Hand-assisted laparoscopic sigmoid resection for diverticular disease: 100 consecutive cases - Wilhelm, Torsten; Refeidi, Ab; Palma, Pablo; Neufang, Thomas; Post, Stefan (Surgical endoscopy and other interventional techniques, 2006)
Hand-assisted laparoscopic surgery (HALS) has been proposed as a useful alternative to conventional laparoscopic and open surgery. As compared with conventional laparoscopic surgery, it offers the advantages of tactile feedback, better exposure, and a shorter learning curve. There is increasing evidence that HALS retains the advantages of minimal-access surgery. The aim of this study was to analyze the feasibility as well as the short- and medium-term outcomes of HALS sigmoid resection for diverticular disease.
Gesehen am 27.05.2022